RANCANG BANGUN SISTEM PEMANEN ENERGI ANGIN EXHAUST FAN DENGAN PENGARUH JARAK TURBIN ANGIN SUMBU HORIZONTAL BILAH EXHAUST FAN - Wr Febriyani, Mawadah; Sukerayasa, I Wayan; Indra Partha, Cokorde Gede (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p22, 2021)
Energy demand in Indonesia is increasing, especially in the realization of electricity consumption which reached 20.18 TWh in July 2020. In fulfilling energy, Indonesia is still supported by fossil energy. Indonesia's fossil energy reserves continue to decline, so it is necessary to increase the non-fossil energy, one of which is wind energy. Wind exhaust fan output is waste energy that has the potential to be developed as a micro-scale wind power plant. The Design and Construction of the Exhaust Fan Wind Energy Harvesting System with the Effect of the Horizontal Axis Wind Turbine Distance (HAWT) of the Exhaust Fan Blade has been done, the test of this study determine the optimal output power of the generator by considering the exhaust fan performance. The test results show that the closest distance of 10 cm produces maximum wind speed and power, but the optimal placement distance for the turbine designed is 20 cm with an output power of 1.50 Watt and an increase in exhaust fan consumption power of 0.38, with the power that can be harvested is 1.50-0.38 = 1.12 Watt, greater than the other test distances.